Hubungan Antara Aktivitas Fisik Dengan Tingkat Kesepian pada Lanjut Usia di Karang Lansia Bahagia Banjarmasin - Fitriana, Laila Noor; Lestari, Dhian Ririn; Rahmayanti, Devi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Changes in elderly include physical, psychological, and social. Physical changes in elderly could affect theirregular physical activity and impact to social and psychological. Psychological and disability can lead toloneliness. The purpose of this study is to describe the correlations between physical activity and lonelinesson elderly at Karang Lansia Bahagia Banjarmasin. This study used analytical survey design and crosssectional. The sample was 33 of elderly aged ≥65 old years, and selected using non-probability samplingtechnique. Instruments of physical activity was Physical Activity Scale for Elderly, and instruments ofloneliness was UCLA Loneliness Scale Version 3. Analysis data used Spearman correlation test. The resultof this study showed that there was a correlations between physical activity and loneliness on elderly atKarang Lansia Bahagia Banjarmasin, with p-value = 0.023 <0. 05, and correlation coefficient (r) = -0.396.Someone who had a better physical activity feel less lonely, and conversely.